2016
DOI: 10.7759/cureus.832
|View full text |Cite
|
Sign up to set email alerts
|

An Interventional Study on the Clinical Usefulness and Outcomes of Electroconvulsive Therapy in Medication-Resistant Mental Disorders

Abstract: BackgroundResistance to recommended medications has been an issue in dealing with a number of psychiatric ailments, and it is showing up as an ongoing challenge for contemporary mental health experts. Resistant psychiatric disorders not only increase the morbidity of patients suffering from such severe conditions but also intensify the problems of their caretakers. This has vigorously started to cause the costs to increase for healthcare services. Thanks to electroconvulsive therapy (ECT), we now have an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The only cohort study of ECT was a retrospective review reporting a mean symptom improvement of 42% following treatment, and 35% improvement 12 months later [38]. Pooled together, the case studies for OCD revealed a response rate of 79% (11/14); within those who responded, symptom improvement of 43-95% was achieved [39][40][41][42][43].…”
Section: Ect Results For Ocdmentioning
confidence: 99%
See 1 more Smart Citation
“…The only cohort study of ECT was a retrospective review reporting a mean symptom improvement of 42% following treatment, and 35% improvement 12 months later [38]. Pooled together, the case studies for OCD revealed a response rate of 79% (11/14); within those who responded, symptom improvement of 43-95% was achieved [39][40][41][42][43].…”
Section: Ect Results For Ocdmentioning
confidence: 99%
“…Quantitative follow-up outcomes were reported in 43% of case studies (6/14 patients). In one study [41], three out of five patients were responders following treatment; only one remained a responder at 3-and 6-month follow-up, according to the clinical global impression (CGI) scale (not YBOCS). Another patient relapsed to baseline twice following consecutive cycles of ECT [42].…”
Section: Ect Results For Ocdmentioning
confidence: 99%
“…Also, according to our definition of TRM, a mood stabilizer and an antipsychotic can, but do not have to, have been prescribed concurrently. This is a compromise based on the literature we reviewed (see Table 1): focusing on the 18 articles published since 2000 that are not case reports, seven define TRM based on one failed medication trial 10,48,58,59,63,64,65 ; five define TRM based on two failed medication trials 15,47,53,54,66 ; four define TRM based on three or more failed medication trials 17,46,55,60 ; and, while some mention that medications can be given sequentially or in combination (like we do), only two require a failed combination 45,56 . In this context, we considered whether we should require that a mood stabilizer and an antipsychotic had been used in combination to define TRM.…”
Section: Discussionmentioning
confidence: 99%
“…Our search identified eight open-label clinical trials [49][50][51][52][53][54][55][56] that enrolled three to 22 participants with BD, with four trials also involving participants with other diagnoses. 51,52,54,56 Four trials required a minimum severity of mania based on a scale [52][53][54][55] and six trials required a minimum duration of treatment.…”
Section: Open-label Non-controlled Trialsmentioning
confidence: 99%
“…Due to this, ECT has a certain effect on OCD patients, but it has a less significant effect on refractory patients. The use of ECT has also been associated with significant improvements in refractory OCD in many cases (24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%